European Yearbook on Human Rights 2025 - Czech, Philip; Heschl, Lisa; Luka, Karin; Nowak, Manfred; Oberleitner, Gerd; Tretter, Hannes (European Yearbook on Human Rights, 2026)
Celebrate with the European Yearbook on Human Rights 2025 the 75th anniversary of the European Convention of Human Rights, the 50th anniversary of the Helsinki Final Act, and the 75th anniversary of the Schuman Declaration! Explore with us the profound and lasting impact of the Council of Europe, the European Union and the Organization for Security and Co-operation in Europe, and the human rights instruments adopted and mechanism established under their umbrella while critically examining the current challenges they face. With this critical resource we reaffirm the importance of academic work for advancing and defending human rights and freedoms essential to our shared humanity. Join us in honoring these legacies and committing to a future where justice, security, and dignity are upheld for all!